Analisis Kemampuan Menulis Peserta Didik Kelas I Sekolah Dasar - Dewi, Retno Sintya; Rismayani, Risha; Muslimah, Muslimah; Juliska, Landia Octa (TSAQOFAH, 2023)
This research is a classroom action research, where the study in this journal is one of the elementary schools in Batanghari Regency, Jambi Province. The purpose of this research is to look at the writing skills of the class and what efforts we will make to improve students' writing skills. The research was carried out on class I students at SDN 95/I Olak with the number of students studied, namely there were 15 people. With this research, we really hope that it will have a better impact in the future for students, especially in the part that our team researches about students' writing abilities. The method used in this research is a qualitative method. The purpose of using this method is to describe the results of the data in the form of values obtained by students. Within this scope, class I students at SDN 95/I Olak were examined by observation or observation, as well as interviews with related teachers. In the early stages of the research, a pretest was carried out by writing the full name of each student in a post-it. At the beginning of the test there were 8 students who could write their full names besides that they could only write their nicknames and there were even 2 students who could not write their names except copying.